2021
DOI: 10.3171/2020.11.spine201403
|View full text |Cite
|
Sign up to set email alerts
|

Late-week surgery and discharge to specialty care associated with higher costs and longer lengths of stay after elective lumbar laminectomy

Abstract: OBJECTIVE In a healthcare landscape in which costs increasingly matter, the authors sought to distinguish among the clinical and nonclinical drivers of patient length of stay (LOS) in the hospital following elective lumbar laminectomy—a common spinal surgery that may be reimbursed using bundled payments—and to understand their relationships with patient outcomes and costs. METHODS Patients ≥ 18 years of age undergoing laminectomy surgery for degenerative lumbar spinal stenosis within the Cleveland Clinic hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Our work reinforces research performed by Salas-Vega et al. (2021) [42] , who investigated extended LOS following lumbar laminectomy. Salas-Vega and colleagues found that patients with surgical complications, non-home discharge destinations, and surgery performed later in the week were more likely to have an extended LOS.…”
Section: Discussionsupporting
confidence: 91%
“…Our work reinforces research performed by Salas-Vega et al. (2021) [42] , who investigated extended LOS following lumbar laminectomy. Salas-Vega and colleagues found that patients with surgical complications, non-home discharge destinations, and surgery performed later in the week were more likely to have an extended LOS.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, Salas-Vega et al 32 recently demonstrated that, in a cohort of patients undergoing lumbar decompression for spinal stenosis, both LOS and total surgical costs increased with lateweek surgeries and discharge to skilled nursing facility or rehabilitation, likely because of diminished availability of inpatient providers, PT/OT, and case management during these times. Our results suggest that weekend discharges are also significantly problematic and result in both decreased odds of prenoon discharge and increased odds of return to acute care within 30 days.…”
Section: Discussionmentioning
confidence: 96%
“…2,5 A previous study demonstrated patients undergoing spinal surgery later in the week (Thursday/ Friday) and NHD patients both experienced significantly increased LOS even after adjusting for patient comorbidities and other patient factors. 6 Similarly, Dasenbrock et al, 7 found increased patient age, patient race, ASA class, and NHD to be significant predictors of eLOS after craniotomy for tumor resection.…”
mentioning
confidence: 95%
“…8 These findings align with conclusions from the literature that optimizing surgical scheduling and care coordination may improve outcomes and lower associated surgical costs. 6,7…”
mentioning
confidence: 99%
See 1 more Smart Citation